Bioaccumulation of PCBs, OCPs and PBDEs in Marine Mammals From West Antarctica - Mohammed Khairy; Emily Brault; Rebecca Dickhut; Karin C. Harding; Tero Harkonen; Olle Karlsson; Kristine Lehnert; Jonas Teilmann; Rainer Lohmann (Frontiers in Marine Science, 2021)
Graphical Abstract POPs in Antarctic Mammals.